Pre-season injury and illness associations with perceptual wellness, neuromuscular fatigue, sleep and training load in elite rugby union - Jones, C. M.; Griffiths, P. C.; Towers, C.; Claxton, J.; Mellalieu, S. D. (Journal of Australian Strength and Conditioning, 2018)
The aim of this study was to investigate injury and illness associations with perceptual wellness, neuromuscular fatigue, sleep and training load in an elite rugby union team during pre-season. During an 11-wk pre-season, 51 elite rugby union athletes were monitored twice-a-week for physiological (sleep quality, energy, muscle soreness) and psychological perceptual wellness (mood), self-reported sleep hours and counter-movement jump height. Training load was estimated via h/athlete/wk. for all training activities. Risk ratios were used to assess weekly injury and illness risk, with effect sizes comparing differences in injury and illness severity above and below thresholds of group mean fatigue and training load measures. Probability of effects were assessed using clinical chances and qualitative inferences. Day 1 perceptual sleep quality and energy were associated with increased illness incidence (Risk ratio = 8.5; Very likely) and severity (Effect sizes = 1.15-1.71; Likely-Very likely) but not injury. Sleeping <8.1 h prior to day 1 was associated with both increased injury and illness incidence (Risk ratios = 2.7-4.2; Likely-Very likely) and severity (Effect sizes = 0.39-1.11; Possibly-Likely). Total training (>8.8-h/athlete/wk.) and resistance training (>3.4-h/athlete/wk.) thresholds were associated with increased injury and injury/illness combined incidence (Risk ratios = 1.8-5.2; Likely-Very likely) and severity (Effect sizes = 0.40-1.12; Possibly-Likely) but not for illness alone. Decreases in day 1 counter-movement jump height preceded spikes in injury in weeks 4 and 7. Simple fatigue and load measures showed potential for informing management of training to minimise injury/illness during an intense rugby union pre-season.